DISASTER INFORMATION SYSTEM FOR MANAGING OVERFLOW FLOOD DISASTER - Prayoga, Yohanes Ary; Sumartono, Christrijogo; Widodo, Suko; Eduard, Stephanus Maria; Kurniawan, Ficky Adi (Universitas Airlangga, 2025)
ndonesia is located at the confluence of active tectonic plates, active mountain ranges, and tropical climates; thus making most of its territory vulnerable to natural disasters. Based on the theory and concept of disaster management which includes several stages, namely: the emergency response phase, the reconstruction and rehabilitation phase, the preventive and mitigation stages, and the preparedness stage, disaster management efforts must be supported by a system. Adequate disaster information in accordance with the characteristics of potential hazards and disaster threats based on analysis and recorded history of disaster events. A good disaster information system is very helpful to the Disaster Management Operations Control Center in conveying suggestions and suggestions for determining policies and coordinating disaster management, distributing logistics, determining evacuation locations, and post-disaster rehabilitation and reconstruction.